The Smallest Anthropoids 2009
DOI: 10.1007/978-1-4419-0293-1_14
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Kinematics of Trunk-to-Trunk Leaping in Callimico goeldii, Callithrix jacchus, and Cebuella pygmaea

Abstract: Callitrichids are characterized by a highly variable positional repertoire, which includes prehensile behaviors on small, flexible supports, and claw-clinging, scansorial travel, and trunk-to-trunk leaping that commonly occurs on large noncompliant supports. In this study, we examine the kinematics of trunk-to-trunk leaping in callimico (C. goeldii), the common marmoset (Callithrix jacchus), and the pygmy marmoset (Cebuella pygmaea). In the wild, each species is reported to exploit vertical trunks during locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
(42 reference statements)
2
18
0
Order By: Relevance
“…Youlatos () examined the positional behavior of six sympatric Ecuadorian primates and also found that small tegulae‐bearing callitrichids showed the highest proportions of large vertical support use. This was attributed to requirements for exudativory but, again, no values are given for the proportion of exudates in the different species' diets, supporting only observations in Garber et al (, ) that the presence of tegulae in callitrichids is linked to vertical foraging behavior. The advantages of claws and claw‐like nails in vertical substrate foraging were suggested to be of particular importance for smaller‐bodied species that regularly utilize vertical, large‐diameter surfaces, where they facilitate extra grip to compensate for limbs which have too short a reach to allow an effective contact angle to be subtended (Soligo and Martin, ; Jackson, ).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Youlatos () examined the positional behavior of six sympatric Ecuadorian primates and also found that small tegulae‐bearing callitrichids showed the highest proportions of large vertical support use. This was attributed to requirements for exudativory but, again, no values are given for the proportion of exudates in the different species' diets, supporting only observations in Garber et al (, ) that the presence of tegulae in callitrichids is linked to vertical foraging behavior. The advantages of claws and claw‐like nails in vertical substrate foraging were suggested to be of particular importance for smaller‐bodied species that regularly utilize vertical, large‐diameter surfaces, where they facilitate extra grip to compensate for limbs which have too short a reach to allow an effective contact angle to be subtended (Soligo and Martin, ; Jackson, ).…”
Section: Discussionmentioning
confidence: 60%
“…Where several studies had comparably collected/described data, average values were calculated. Data were collated from results in the following studies: Garber, 1 ; da Fonseca and Lacher, 2 ; Garber and Sussman, 3 ; Yoneda, 4 ,b; Garber, 5 ; Ayres and Clutton‐Brock, 6 ; Egler, 7 ; Ferrari and Strier, 8 ; Garber, 9 ; Peres, 10 ; Rosenberger, 11 ; Garber, 12 ; Peres, 13 ; Lopes and Ferrari, 14 ; Peres, 15 ; Garber and Pruetz, 16 ; Ferrari and Digby, 17 ; Dietz et al, 18 ; Peres, 19 ; Garber, 20 ; Hamrick, 21 ; Youlatos, 22 ; Araújo et al, 23 ; Corrêa et al, 24 ; Heymann and Buchanan‐Smith, 25 ; Heymann et al, 26 ; Martins and Setz, 27 ; Oliveira and Ferrari, 28 ; Garber and Leigh, 29 ; Miranda and Faria, 30 ; Porter, 31 ; Regan et al, 32 ; Lehman, 33 ; Porter, 34 ; Poveda and Sanchez‐Palomino, 35 ; Raboy and Dietz, 36 ; Bicca‐Marques, 37 ; Garber et al, 38 ; Yépez et al, 39 ; Cunha et al, 40 ; Burity et al, 41 ,; da Silva and Ferrari, 42 ; de Castro and Araújo, 43 ; Digby et al, 44 ; Garber, 45 ; Lapenta and Procópio‐de‐Oliveira, 46 ; Nadjafzadeh and Heymann, 47 ; Porter et al, 48 ; Raboy et al, 49 ; Garber et al, 50 ; Garber and Porter, 51 ; Porter et al, 52 ; Rehg, 53 ; Veracini, 54 ; Youlatos, 55 ; Hilário and Ferrari, 56 ; Porter and Garber, 57 ; Smith, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on these initial adaptations, many primate species have evolved derived postural and locomotor traits including forelimb elongation associated with the demands of suspensory postures in the apes, claw-like nails for vertical clinging in callitrichines, prehensile tails in atelines and capuchins, and hindlimb elongation facilitating movement on vertical supports in several smaller-bodied taxa. These features serve a critical role in habitat utilization and resource acquisition [Bezanson, 2012;Cant, 1987;Garber, 1991Garber et al, 2009;Godfrey & Jungers, 2003;Larson, 1998;Niemitz, 1984]. Correction added on September 17, 2014, after first online publication: Table 1 was corrected.…”
Section: Introductionmentioning
confidence: 91%
“…Callimico is very specialized postcranially, especially in the hind limbs and ankle joint, which are designed to facilitate increased leaping by providing the necessary mechanical advantage and required stability for load resistance (Ford,1988; Garber and Leigh,2001; Davis,2002; Garber et al;2005,2009). Behaviorally, callimicos exhibit particularly high rates of leaping, most of which are vertical leaps (Garber et al;2005,2009), while quadrupedalism, climbing and clawed locomotion are used in a lesser degree (Garber and Leigh,2001). These patterns appear to be ecologically associated with the exploitation of the lower forest strata with abundant vertical supports, where they frequently forage for arthropods and collect fruit and fungi (Porter and Garber,2004).…”
Section: “Dwarves and Claws”mentioning
confidence: 99%